Measurement of Human Physical Work using Biomechanical Approach with RULA and REBA Methods in PT. Cemindo Gemilang - Vidi Agung Fragastia Vidi Agung Fragastia; Alam Taufik Siregar (Industrial Engineering System and Management Journal, 2024)
This research aims to increase productivity and identify potential risks of musculoskeletal injuries to workers at PT. Cemindo Gemilang. The RULA (Rapid Upper Limb Assessment) and REBA (Rapid Entire Body Assessment) methods are used to analyze work posture and physical loads experienced by workers. The biomechanical approach is used as a framework for understanding the interactions between workers, tools, and the work environment. By measuring human physical work using the RULA and REBA methods, non-ergonomic work postures and the level of risk of musculoskeletal injuries associated with work activities in cement factories can be identified. The results of this research can provide recommendations for improving tool design, rearranging work spaces, and changing work procedures to reduce the risk of musculoskeletal injuries and increase worker productivity. By implementing the recommendations resulting from this research, it is hoped that PT. Cemindo Gemilang can achieve safer, more efficient and more productive working conditions.